Sub-Micrometer Scale Surface Roughness of Titanium Reduces Fibroblasts Function. Issue 1 (April 2016) - Migita, Satoshi; Okuyama, So; Araki, Kunitaka
Titanium and its alloys are conventionally used to produce medical devices, but their biocompatibility has not yet been optimized. Surface modification, especially control of the surface roughness of titanium, is one strategy for improving biocompatibility and providing effective binding to hard tissue. However, the soft tissue compatibility of metallic materials is currently poorly understood, and effective techniques for tight binding between metal surfaces and soft tissue are still under development. Therefore, we here investigated whether the surface roughness of titanium affects fibroblast adhesion and proliferation. Our results showed that a surface roughness of ∼100 nm reduces fibroblast function. On such surfaces, distinct focal adhesion was not observed. These findings improve the general understanding of the binding compatibility between soft tissues and metallic materials.